Changes of circulating biomarkers of inflammation and glycolipid metabolism by CPAP in OSA patients: a meta-analysis of time-dependent profiles. (January 2022) - Wang, Yi; Lin, Ying Ni; Zhang, Li Yue; Li, Chuan Xiang; Li, Shi Qi; Li, Hong Peng; Zhang, Liu; Li, Ning; Yan, Ya Ru; Li, Qing Yun
Background: Continuous positive airway pressure (CPAP) is the first-line therapy for moderate-to-severe obstructive sleep apnea (OSA). Specifying timing of CPAP benefits on OSA-related biomarkers will help to assess the effectiveness of CPAP and to optimize the treatment strategies. Purpose: To explore the time-dependent changes of circulating biomarkers to CPAP treatment in patients with OSA, including inflammatory biomarkers [C-reactive protein (CRP) and tumor necrosis factor–α (TNF-α)] and glycolipid metabolic biomarkers [fasting blood glucose (FBG), fasting insulin (FINS), low-density lipoprotein (LDL), high-density lipoprotein (HDL), total cholesterol (TC), and triglyceride (TG)]. Methods: Searches of PubMed and Embase database were completed. Two independent reviewers extracted data from 68 included studies. A meta-analysis was conducted using a random-effect (or fixed-effect) model and standardized mean difference (SMD) model. The timing profiles of circulating biomarkers changes of inflammation and glycolipid metabolism were analyzed based on different CPAP duration, that is, short-term (<3 months), mid-term (3–6 months), and long-term (⩾6 months). Results: Those first improved by short-term treatment include CRP [SMD: 0.73, 95% confidence interval (CI): 0.15–1.31; p  = 0.014], TNF-α [SMD: 0.48 (95% CI: 0.10–0.86; p  = 0.014)], FBG [SMD: 0.32 (95% CI: 0.07–0.57; p  = 0.011)], and LDL [SMD: 0.40 (95% CI: 0.18–0.62; p  = 0.000)]. Those first improved by the mid-term or long-term treatment include HDL [SMD: –0.20 (95% CI: –0.36 to –0.03; p  = 0.018)] and TC [SMD: 0.20 (95% CI: 0.05–0.34; p  = 0.007)]. There were insignificant changes for TG and FINS after short or long CPAP. Conclusion: Our results imply that changes of circulating biomarkers for patients with OSA under CPAP treatment have a time-dependent profile.